Readiness of Nursing Profession Students Universitas Padjadjaran on Handling Emergency Patients in Emergency Department - Efri Widianti; Retno Wahyuningsih; Etika Emaliyawati (Universitas Padjadjaran, 2020)
Nursing profession students need readiness to attend profession learning. Optimal readiness is directly proportional to optimal capabilities. The characteristics of emergency department tend to make nursing profession students the first and most frequent resource to deal with patients entering the emergency department. This study aims to determine the readiness of nursing profession students on handling emergency patients in emergency department.This study uses quantitative descriptive methods through approaches cross sectional. The population in this study was a nursing profession students of the Faculty of Nurisng, Universitas Padjadjaran as many as 66 respondents. The total sampling technique was used in this study. This research measuring instrument uses the READI-JV The results of the study were calculated using quantitative descriptive analysis using a cross-sectional approach.The results showed that as many as 51 (77.3%) nursing profession students are not ready to handle emergency patients. The percentage of readiness obtained in the leadership and administrative support dimensions was 85.2%, the readiness obtained in the operational competency dimension was 63.9%, the readiness obtained in the establishment dimension was 63.1%, the readiness obtained in the stress handling dimension was 57.6%, the readiness obtained in the dimensions of group integration and identification of 57.5%, readiness obtained in the survival skills dimension was 56.6%, and readiness obtained in the clinical competency dimension was 47.2%.The unpreparedness of nursing profession students is because most of the respondents have not attended emergency department training. So that it is necessary to optimize the learning methods during pre- profession by applying in accordance with emergencies and based on case studies as well as providing stress management to students to reduce stress levels in nursing profession students.